VIRAL DETECTION IN TICKS AND THE LEVEL OF TICKS’ INFESTATIONS AMONGST SMALL RUMINANTS IN MAIDUGURI, BORNO STATE - GHAMBA, PETER E.; J. GOJE, LAZARUS; SHERIFF, AISHATU B. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
Ticks were the first arthropods to be established as vectors of pathogens and are currently recognized, along with mosquitoes, as the main arthropod vectors of disease agents to humans and domestic animals globally due to increased incidences of tick-borne diseases (TBDs) the world over. They are responsible for the transmission of many viral diseases to humans and domestic animals. Therefore, ticks infection and infestation results in great economic losses to resource-poor farming communities, especially in tropical and subtropical regions, including Nigeria, where approximately 80% of the world’s cattle population is raised. The current study is aimed to study the distribution, composition and abundance of ticks in Maiduguri, Borno State. Adult ticks were collected from 350 freshly butchered small ruminants (sheep and goats) from three locations within Maiduguri metropolis namely: Kasuwa shanu, Bulumkutu, and Maiduguri Central Abattoir. These were identified using taxonomy identification keys in to three species, Rhipicephalus, Amblyomma and Hyalomma, using stereomicroscope for each of the locations. They were crushed using bullet blender after the addition of glass beads and centrifuged. The supernatant from the crushed samples was used for viral detection by inoculating it on to two cell lines, Baby Hamster Kidney (BHK) and African Monkey Kidney (Vero E6), and were observed for cytopathic effects daily for a period of ten (10) days. The results showed a high level of ticks’ infestation amongst small ruminants in the study locations. Kasuwan Shanu has the highest distribution of ticks amongst sheep, followed by Maiduguri Central Abattoir while Bulumkutu has the least. More also, Kasuwan Shanu has the highest distribution of ticks amongst goats, followed by Bulumkutu while Maiduguri Central Abbatoir has the least. The three species of ticks investigated were found to comprise of either male or female or both in the different locations, and either of the two sexes is involved in the infestation. The results also showed the presence of virus in some of the tick samples isolated from the small ruminants and inoculated on to the cell lines due to the observed cytopathic effects. It is concluded that there is high level of ticks’ infestation among small ruminants in Maiduguri metropolis and a threat of viral disease transmission to humans and other animals. Keywords: